An Adaptive Measure of Visuospatial Impairment in Dementia with Lewy Bodies. Issue 5 (13th June 2022) - Phillips, Joseph R.; Matar, Elie; Ehgoetz Martens, Kaylena A.; Moustafa, Ahmed A.; Halliday, Glenda M.; Lewis, Simon J.G.
ABSTRACT: Background: Dementia with Lewy bodies (DLB) is a common cause of dementia with poor prognosis and high hospitalization rates. DLB is frequently misdiagnosed, with clinical features that overlap significantly with other diseases including Parkinson's disease (PD). Clinical instruments that discriminate and track the progression of cognitive impairment in DLB are needed. Objectives: The current study was designed to assess the utility of a mental rotation (MR) task for assessing visuospatial impairments in early DLB. Methods: Accuracy of 22 DLB patients, 22 PD patients and 22 age‐matched healthy controls in the MR task were compared at comparing shapes with 0°, 45° and 90° rotations. Results: Healthy controls and PD patients performed at similar levels while the DLB group were significantly impaired. Further, impairment in the visuospatial and executive function measures correlated with MR poor outcomes. Conclusion: These findings support the MR task as an objective measure of visuospatial impairment with the ability to adjust difficulty to suit impairments in a DLB population. This would be a useful tool within clinical trials.